Current Progress in Microbial Biocontrol of Banana Fusarium Wilt: A Systematic Review - Solórzano Acosta, Richard Andi (2025)
Fusarium oxysporum f. sp. cubense (Foc) poses a significant threat to global banana production. This systematic review updates current knowledge on the efficacy of various antagonistic microorganisms in controlling Foc, considering the recent spread of this disease to new regions. The studies were systematically analyzed, focusing on methodologies, results, and conclusions to provide a comprehensive overview of current research and its practical implications. A total of 118 studies were reviewed, covering the use of antagonistic microorganisms such as Trichoderma spp., Bacillus spp., Streptomyces spp., and Pseudomonas spp., both in pure cultures and in consortia. Most studies focused on controlling Foc TR4 in Cavendish subgroup bananas and originated from Asia. Microbial consortia demonstrated a higher control percentage with lower variability, particularly in genera such as Pseudomonas. In contrast, pure cultures were more commonly used for Streptomyces. The choice between consortia and pure cultures depends on the genus and the experimental context, as each approach has distinct advantages. Although the reviewed studies were generally of high quality, long-term research is still lacking. Antagonistic microorganisms represent a promising alternative for Foc control, although their efficacy depends on the specific strain and environmental conditions. It has been observed that inoculating these microorganisms onto seedlings before transplantation or in combination with organic matter enhances their effectiveness. Localized testing and formulation optimization are recommended to improve their application as preventive and suppressive tools in soil against infections. The review highlights a vast diversity of microbial agents with high efficacy rates, various modes of action, and additional benefits for plant development beyond Foc biocontrol. Furthermore, some studies achieved 100% control at the plant level under controlled conditions. These findings demonstrate that biological control is a viable alternative for integrated Foc management. Future research should prioritize new approaches that facilitate the widespread adoption of these methodologies, including microbial formulation, field application, and integration with other control methods.